Continuous improvement of outsourcing processess: the experience of an electric power distributor - Pinho, José Ocelo Maciel (2012)
The present work aims at analyzing how continuous improvement is developed in the outsourced processes of an electric power distribution company. The study brings a summary of outsourcing highlighting the complexity and difficulty of such a process as well as the importance of a partnership between taker and service provider. Results obtained indicate that in order continuously improve outsourced processes, essential factors must be consideredamong them: well defined service level agreements contract, selection of service providers with expertise in the activity, partnership formation and systematic evaluation of partner companies.